Levoketoconazole in the Treatment of Patients With Cushing’s Syndrome and Diabetes Mellitus: Results From the SONICS Phase 3 Study - Pivonello, Rosario; Elenkova, Atanaska; Fleseriu, Maria; Feelders, Richard A.; Witek, Przemyslaw; Greenman, Yona; Geer, Eliza B.; Perotti, Paola; Saiegh, Leonard; Cohen, Fredric; Arnaldi, Giorgio (Frontiers in Endocrinology, 2021)
Background Cushing’s syndrome (CS) is associated with numerous comorbidities, including diabetes mellitus (DM). Levoketoconazole, an orally administered ketoconazole stereoisomer, is in clinical trials for the treatment of CS. Methods SONICS, a prospective, open-label, phase 3 study in adults with confirmed CS and mean 24-h urinary free cortisol (mUFC) ≥1.5× ULN, included dose-titration, 6-month maintenance, and 6-month extension phases. This subanalysis evaluated the efficacy of levoketoconazole in patients with DM (n = 28) or without DM (n = 49) who entered the maintenance phase. Safety was evaluated in the overall population (N = 94) during the dose-titration and maintenance phases. Results Normalization of mUFC at the end of maintenance phase (EoM), without a dose increase during maintenance (SONICS primary endpoint) was observed in 46% of patients with DM (95% CI, 28 to 66%; P = 0.0006 vs null hypothesis of ≤20%) and 33% of patients without DM (95% CI, 20 to 48%; P = 0.0209). At EoM, mean HbA1c decreased from 6.9% at baseline to 6.2% in patients with DM and from 5.5 to 5.3% in patients without DM. Mean fasting blood glucose decreased from 6.85 mmol/L (123.4 mg/dl) to 5.82 mmol/L (104.9 mg/dl) and from 5.11 mmol/L (92.1 mg/dl) to 4.66 mmol/L (84.0 mg/dl) in patients with and without DM, respectively. Adverse events that were more common in patients with DM included nausea (58.3%), vomiting (19.4%), and urinary tract infection (16.7%); none prompted study drug withdrawal. Conclusions Treatment with levoketoconazole led to sustained normalization of mUFC and improvement in glycemic control that was more pronounced in patients with DM. Clinical Trial Registration (ClinicalTrials.gov), NCT01838551.